Tackling that test : everything you wanted to know about taking tests and exams - Withers, Graeme (Camberwell, Vic. : Australian Council for Educational Research, 1999)
This book is about: Things to ask yourself before your test; Tests and examinations-what's the difference?; Feeling good about a test or an exam; Tactics and strategies before the test session; ...
Keywords: Educational tests; Educational measurements; High schools teaching; Educational tests and measurements -- Australia; High schools -- Australia -- Examinations -- Study guides; Examinations -- Australia -- Study guides